Students' Attitudes on Blended Learning-Based Instruction in Indonesian EFL Classroom - Munir; Muhayyang, Maemuna; Limbong, Sunarlia; Ariyani, Amra (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This study explores the students' attitudes on blended learning-based instruction in Indonesian EFL classrooms. It employs a descriptive study using a purposive sampling technique and taking 34 respondents from EFL university students. The questionnaire and interview were used to collect data on the perception of EFL university students on blended learning-based instruction in the process of learning in the EFL classroom. The result of the study shows the students' perception of the integration of blended learning in the classroom. It falls into some categories: the usefulness of blended learning, the institutional support, the impact of blended learning on the students learning, and the percentage use of blended learning as well as challenges encountered in using blended learning. This research is expected to be of benefit to lecturers, students, and stakeholders to enrich knowledge and develop language skills and proficiency based on blended learning instruction in the Indonesian EFL classroom.